Advanced sublimation source for CdTe photovoltaics - Tapparo, Marc, author; Sampath, Walajabad, advisor; Munshi, Amit, committee member; Sites, Jim, committee member (Colorado State University. Libraries, 2025)
This thesis presents the design, modeling, and validation of an advanced sublimation source for cadmium telluride (CdTe) thin-film photovoltaic (CPV) manufacturing, to improve thermal uniformity, system maintainability, and compatibility with Colorado State University's Advanced Research Deposition System (ARDS). Traditional heater configurations in close-space sublimation (CSS) processes have relied on nichrome (NiCr) heater coils cemented to graphite. These are prone to failure from thermal voids in the ceramic cement, dielectric breakdown, and complex maintenance and procedures. After several iterations a new source design incorporating split-sheath cartridge heaters used in the industry was developed and evaluated to address these limitations. Steady-state thermal simulations in finite element software, ANSYS Mechanical, were performed to assess the impact of heater layout, graphite source geometry, and power distribution on temperature uniformity in the CdTe vapor region. G330 graphite with a thermal conductivity of 107 W/m·K was modeled. The effect of shielding and power output of the heater was included in the simulations. The simulations showed thermally uniform sources all within acceptable limits to meet a ±10% deposition uniformity. The simulations showed that a 1.25″ thick bottom plate produced the most uniform isothermal distribution, with less than 5 °C temperature variation across the region. These results were validated through experimental deposition and profilometry, which revealed ±2.9% thickness variation in CdTe films under typical processing conditions. In contrast to prior CSU designs, such as the cemented NiCr configuration, the split-sheath system demonstrated improved thermal stability, maintainability, and resistance to arcing under vacuum. This work confirms that split-sheath heaters and optimized source geometry offer a scalable and resilient solution for precision sublimation in next-generation CdTe PV manufacturing platforms.
Keywords: close space sublimation; CdTe